Recent sexual violence exposure is associated with immune biomarkers of HIV susceptibility in women. (10th May 2021) - Aldous, Annette M.; Joy, Christopher; Daniels, Jason; Jais, Mariel; Simmens, Samuel J.; Magnus, Manya; Roberts, Afsoon; Connors, Kaleigh; Capozzi, Brendan; Mohamed, Hani; Juzumaite, Monika; Devore, Heather; et al.
Abstract: Problem: HIV/AIDS and sexual violence act synergistically and compromise women's health. Yet, immuno‐biological mechanisms linking sexual violence and increased HIV susceptibility are poorly understood. Methods: We conducted a cross‐sectional pilot study of HIV‐uninfected women, comparing 13 women exposed to forced vaginal penetration within the past 12 weeks (Exposed) with 25 Non‐Exposed women. ELISA assays were conducted for 49 biomarkers associated with HIV pathogenesis in plasma and cervicovaginal lavage (CVL). Differences between Exposed and Non‐Exposed were analyzed by linear and logistic regression, using propensity score weighting to control for age, race, socioeconomic status, menstrual cycle, and contraceptive use. Results: In CVL, Exposed women had significantly reduced chemokines MIP‐3α ( p  < .01), MCP‐1 ( p  < .01), and anti‐HIV/wound‐healing thrombospondin‐1 ( p  = .03). They also had significantly increased inflammatory cytokine IL‐1α ( p < 0.01) and were more likely to have detectable wound‐healing PDGF ( p  = .02). In plasma, Exposed women had reduced chemokines MIP‐3α ( p  < .01) and IL‐8 ( p  < .01), anti‐inflammatory cytokine TGF‐β ( p  = .02), anti‐HIV/antimicrobial HBD–2 ( p  = .02), and wound‐healing MMP‐1 ( p  = 0.02). They also had increased thrombospondin‐1 ( p  < .01) and Cathepsin B ( p  = .01). After applying the stringent method of false discovery rate adjustment, differences for IL‐1α ( p  = .05) and MCP‐1 ( p  = .03) in CVL and MIP‐3α ( p  = .03) in plasma remained significant. Conclusions: We report systemic and mucosal immune dysregulation in women exposed to sexual violence. As these biomarkers have been associated with HIV pathogenesis, dysregulation may increase HIV susceptibility.